Developmental Pathways Through Middle Childhood : Rethinking Contexts and Diversity as Resources. (Taylor & Francis, 2005)
This volume looks at the study of successful pathways through middle childhood. The chapters look at how diverse environmental contexts (economic, culture, history, politics) influence child and family development.